2017
DOI: 10.1152/jn.00490.2016
|View full text |Cite
|
Sign up to set email alerts
|

Modeling fast and slow gamma oscillations with interneurons of different subtype

Abstract: Experimental and theoretical studies demonstrate that neuronal gamma oscillations crucially depend on interneurons, but current models do not consider the diversity of known interneuron subtypes. Moreover, in CA1 of the hippocampus, experimental evidence indicates the presence of multiple gamma oscillators, two of which may be coordinated by differing interneuron populations. In this article, we show that models of networks with competing interneuron populations with different postsynaptic effects are sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 68 publications
(115 reference statements)
4
60
0
Order By: Relevance
“…These two ingredients usually characterize real brain networks, where our prediction that slow (fast) γ oscillations are associated with more (less) irregular neuronal dynamics can be experimentally tested, e.g., by measuring the coefficient of variation associated with these two states. Furthermore, previous theoretical analysis of γ oscillations based on two interacting Wilson-Cowan rate models with different synaptic times revealed only the possible coexistence of two stable limit cycles, both corresponding to tonic collective firing, i.e., mean-driven COs [54].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…These two ingredients usually characterize real brain networks, where our prediction that slow (fast) γ oscillations are associated with more (less) irregular neuronal dynamics can be experimentally tested, e.g., by measuring the coefficient of variation associated with these two states. Furthermore, previous theoretical analysis of γ oscillations based on two interacting Wilson-Cowan rate models with different synaptic times revealed only the possible coexistence of two stable limit cycles, both corresponding to tonic collective firing, i.e., mean-driven COs [54].…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, there is experimental evidence that γ rhythms can be generated locally in vitro in the CA1, as well as in the CA3 and mEC, due to optogenetic stimulations [39,48,49] or pharmacological manipulations, but at lower γ frequencies with respect to optogenetics [50][51][52][53]. A recent theoretical work has analyzed the emergence of γ oscillations in a neural circuit composed of two populations of interneurons with fast and slow synaptic timescales [54]. Based on the results of this idealized rate model and on the analysis of experimental data sets for the CA1, the authors showed that multiple γ bands can arise locally without being the reflection of feedforward inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Then, to investigate the existence of a fully synchronized state, we can drop the index j in Eq. (12). Note that, in the absence of coupling, Eq.…”
Section: The Fully Synchronized Statementioning
confidence: 98%
“…where R represents the mean firing rate in the population, S is the synaptic activation, and the time constants τ m and τ d are the neuronal and synaptic time constants respectively [39,43]…”
Section: A a Heuristic Firing Rate Equationmentioning
confidence: 99%